Recent advances in 2D organic−inorganic heterostructures for electronics and optoelectronics. Issue 2 (7th November 2022) - Khan, Jahangir; Ahmad, Rana Tariq Mehmood; Tan, Junyang; Zhang, Rongjie; Khan, Usman; Liu, Bilu
Abstract: Two‐dimensional (2D) materials show outstanding properties such as dangling bond‐free surfaces, strong in‐plane while weak out‐of‐plane bonding, layer‐dependent electronic structures, and tunable electronic and optoelectronic properties, making them promising for numerous applications. Integrating 2D inorganics with organic materials to make van der Waals heterostructures at the 2D thickness limit has created new platforms for fabricating on‐demand multifunctional devices. To further broaden the limited choices of 2D inorganic‐based heterostructures, a wide range of available 2D organic materials with tunable properties have opened new opportunities for designing large numbers of heterostructures with 2D inorganic materials. This review aims to attract the attention of researchers toward this emerging 2D organic−inorganic field. We first highlight recent progress in organic−inorganic heterostructures and their synthesis and then discuss their potential applications, such as field‐effect transistors, photodetectors, solar cells, and neuromorphic computing devices. In the end, we present a summary of challenges and opportunities in this field. Abstract : The integration of atomically‐thin 2D inorganic materials with large numbers of available organic materials can create exciting new opportunities for future multifunctional devices. This review summarizes the recent advances in 2D organic−inorganic‐based heterostructures, including their structures, properties, synthesis, and applications in electronic and optoelectronic devices.